Molecular signatures of selection associated with host plant differences in Pieris butterflies. Issue 22 (23rd October 2019) - Okamura, Yu; Sato, Ai; Tsuzuki, Natsumi; Murakami, Masashi; Heidel‐Fischer, Hanna; Vogel, Heiko
Abstract: Adaptive traits that enable organisms to conquer novel niches and experience subsequent diversification are ecologically and evolutionarily important. The larvae of Pieris butterflies express nitrile‐specifier proteins ( NSP s), a key innovation for overcoming the glucosinolate (GLS)‐myrosinase‐based defence system of their Brassicales host plants. Nitrile‐specifier proteins are a member of the NSP ‐like gene family, which includes the major allergen ( MA ) protein, a paralog of NSP with a GLS‐disarming function, and a single domain major allergen ( SDMA ) protein, whose function is unknown. The arms‐race between GLS‐based defences and the NSP ‐like gene family is suggested to mediate diversification in both Pierid butterflies and Brassicales plants. Here, we tested whether the expected strong selection on NSP ‐like gene family correlates with shifts in host plant spectra among Pierid butterflies. We combined feeding experiments using 25 Brassicaceae plants and five Pieris species with larval transcriptome data to investigate the patterns of selection acting on NSP ‐like gene family members. Although we observed significantly elevated nonsynonymous to synonymous substitution rate ratios in NSP s on branches associated with changes in patterns of host plant usage, no such pattern was observed in MA s or SDMA s. Furthermore, we found evidence for positive selection of NSP at a phylogenetic branch which reflects different host plant spectra. Our data indicate that the NSP ‐related gene members have evolved differently: NSP s have accumulated more amino acid changes in response to shifting preferences for host plants, whereas MA s and SDMA s appear to be more conserved. Further detailed functional assays of these genes would provide important insights to understand their role in the chemical arms‐race between Pieris butterflies and their Brassicales host plants.